IMPROVEMENT OF CLEAN WATER PRODUCT QUALITY THROUGH DESINFECTION PROCESS - Munawar Ali; Dwi Sukma Donoriyanto; Nur Rahmawati (Journal of Scientech Research and Development, 2022)
In the process of treating raw water into clean water, the pathogenic bacteria must be eliminated. The process of eliminating pathogenic bacteria which then cause an unpleasant odor can be carried out by disinfection. The thing that needs to be considered in the context of disinfection is how to prevent the transfer of germs to the human body through clean water by breaking the chain between the two by means of disinfection. This research begins with a laboratory test of the total coliform content in water treated by Biofilter without disinfection. The laboratory test results showed that the content of Fecal Coli was 1880/100 ml and the bacteria in the Coli group were 2060/100 ml. This parameter must be reduced to the limit according to the Environmental Quality Standard (BML) using a disinfection treatment. From the observations made on the coagulation process from raw water it can be informed that in the range of observed variables, with an increase in the dose of Calcium Hypochlorite (Ca (OCl) 2) from 1 mg / lt to 3 mg / l in the disinfection process, the number of E. coli bacteria which is being lowered more and more. At a dose of Calcium Hypochlorite Ca (OCl) 2 2.5 mg in 1 liter of raw water for the Kebon Agung Canal Drainage Channel with a stirring time of 30 minutes was able to reduce the number of E. Coli bacteria by 99, 40%.